A molecular diagnostic tool for the preliminary assessment of host–parasitoid associations in biological control programmes for a new invasive pest. Issue 15 (22nd October 2013) - Gariepy, T. D.; Haye, T.; Zhang, J.
Abstract Evaluation of host–parasitoid associations can be tenuous using conventional methods. Molecular techniques are well placed to identify trophic links and resolve host–parasitoid associations. Establishment of the highly invasive brown marmorated stink bug, Halyomorpha halys (Hemiptera: Pentatomidae), outside Asia has prompted interest in the use of egg parasitoids (Hymenoptera: Scelionidae) as biological control agents. However, little is known regarding their host ranges. To address this, a DNA barcoding approach was taken wherein general PCR primers for Scelionidae and Pentatomidae were developed to amplify and sequence >500‐bp products within the DNA barcoding region of the cytochrome oxidase I (COI) gene that would permit the identification of key players in this association. Amplification of DNA from Pentatomidae and Scelionidae was consistent across a broad range of taxa within these families, and permitted the detection of Scelionidae eggs within H. halys 1 h following oviposition. In laboratory assays, amplification and sequencing of DNA from empty, parasitized eggs was successful for both host (100% success) and parasitoid (50% success). When applied to field‐collected, empty egg masses, the primers permitted host identification in 50–100% of the eggs analysed, and yielded species‐level identifications. Parasitoid identification success ranged from 33 to 67% among field‐collected eggs, with genus‐level identification for most specimens. The inability to obtain species‐level identities for these individuals is due to the lack of coverage of this taxonomic group in public DNA sequence databases; this situation is likely to improve as more species are sequenced and recorded in these databases. These primers were able to detect and identify both pentatomid host and scelionid parasitoid in a hyperparasitized egg mass, thereby clarifying trophic links otherwise unresolved by conventional methodology.